Implementasi Akuntansi Nirlaba Berdasarkan PSAK No. 45 (Studi Kasus Pada Masjid Muthohhirin di Yogyakarta) - Hapsari, Wahyu Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
A non-profit entity is an entity that does not aim to make a profit. Mosques are a form of non-profit entity. Mosques in the current era are no longer just for worship, but are social, educational and economic centers. This research aims to determine financial management in mosques and see the recording based on standards issued by the Indonesian Accounting Association (IAI), namely PSAK 45. The research object is the Muthohhirin Mosque, Yogyakarta. The author uses qualitative methods. Data collection was carried out by interviews and documentation. Interviews were conducted with the mosque treasurer and takmir. The results of this research show that mosque administrators have managed finances openly by recording cash receipts and disbursements. The Financial management of the Muthohhirin mosque is well recorded in simple form. The mosque management has not recorded according to PSAK 45 because the takmir has never been know of the existence of PSAK 45 as a standard for financial recording in mosques.